2004
DOI: 10.1111/j.1467-9817.2004.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Good readers but at a cost? Attitudes to reading in England

Abstract: The results of the Progress in International Reading Literacy Study 2001 (PIRLS) were reported in 2003. In addition to data about the reading achievements of 10-year-olds in 35 countries, the study also collected questionnaire information from children, their teachers, headteachers and parents. One aspect of the data that attracted comment in the media was the fact that, despite high achievement on the reading tests, children in England were reported as having relatively poor attitudes to reading, compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 4 publications
2
28
0
1
Order By: Relevance
“…England (Twist et al, 2003(Twist et al, , 2007, the reduction in primary phase book spending (Hurd et al, 2006), and the lack of teacher knowledge of children's literature evidenced in this research, there is a real need for increased professional attention and support in this area. Practitioners need ongoing opportunities to enrich this critical knowledge base and need to know how and where to access advice about books and writers.Whilst librarians could be central to this, evidence both in the US and in England, suggests their expertise is not well utilised (Ofsted, 2004;Ross, McKechnie and Rothbauer, 2006;Cremin et al, 2007b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…England (Twist et al, 2003(Twist et al, , 2007, the reduction in primary phase book spending (Hurd et al, 2006), and the lack of teacher knowledge of children's literature evidenced in this research, there is a real need for increased professional attention and support in this area. Practitioners need ongoing opportunities to enrich this critical knowledge base and need to know how and where to access advice about books and writers.Whilst librarians could be central to this, evidence both in the US and in England, suggests their expertise is not well utilised (Ofsted, 2004;Ross, McKechnie and Rothbauer, 2006;Cremin et al, 2007b).…”
Section: Discussionmentioning
confidence: 99%
“…The earlier PIRLS study, which involved comparing ten year olds in 35 countries, revealed that 13% of the English children disliked reading, compared to 6% on average. When asked how confident they were about reading, only 30% rated themselves as highly confident, compared to an international average of 40% (Mullis et al, 2003;Twist et al, 2003). In the 2006 study, which involved 41 countries, only 28% of the English children reported reading weekly compared to an international average of 40%.…”
Section: Introductionmentioning
confidence: 99%
“…So, a reading habit could be considered as a behavioural manifestation of a reading attitude: an established habit would imply a positive orientation towards reading, entailing some sort of personal satisfaction that reinforces the act of being a reader (Larrañaga & Yubero, 2005). It is precisely the lack of a consistent definition of reading attitude in the studies on the subject that has led to searching for more objective variables, such as reading Teachers as readers / El docente como lector 45 habits, to avoid the mere report of feelings or intentions for the study of reading behaviour (Mathewson, 1994;Petscher, 2010;Twist, Gnaldi, Schagen, & Morrison, 2004). In turn, attitude influences the participants' involvement in reading and, therefore, it becomes associated with motivation, considered to be a requirement for initiating and sustaining this activity (Alexander & Filler, 1976;Mathewson, 1994;Twist et al, 2004;Wigfield & Guthrie, 1997).…”
Section: Habits Attitude and Reading Motivationmentioning
confidence: 98%
“…It is precisely the lack of a consistent definition of reading attitude in the studies on the subject that has led to searching for more objective variables, such as reading Teachers as readers / El docente como lector 45 habits, to avoid the mere report of feelings or intentions for the study of reading behaviour (Mathewson, 1994;Petscher, 2010;Twist, Gnaldi, Schagen, & Morrison, 2004). In turn, attitude influences the participants' involvement in reading and, therefore, it becomes associated with motivation, considered to be a requirement for initiating and sustaining this activity (Alexander & Filler, 1976;Mathewson, 1994;Twist et al, 2004;Wigfield & Guthrie, 1997). More specifically, related reading motivation to attitude through two components: extrinsic motivation, linked to the consideration of reading as an instrumental activity, which seems to lead the subjects to read while there are external demands, and intrinsic motivation, defined as the disposition to seek out reading activities for the sheer pleasure of them, which sustains the subject's involvement in reading beyond such demands.…”
Section: Habits Attitude and Reading Motivationmentioning
confidence: 99%
“…There was only a very weak association between attitudes and achievement (0.04). Twist et al [107] found some links between attitudes to reading and reading attainment for 200,000 nine-and 10-year-old children in 41 countries in the Progress in International Reading Literacy Study (PIRLS).…”
Section: Other Individualmentioning
confidence: 99%